PEMBANGUNAN PARTISIPATIF DI KOTA BANJARMASIN (Studi Kesesuaian Rencana Kerja Pembangunan Daerah dengan Hasil Musrenbang Tahun Anggaran 2016 di Kecamatan Banjarmasin Tengah) - Anwar Rosshad; Cynthia Winna Widya Putri (J-3P (Jurnal Pembangunan Pemberdayaan Pemerintahan), 2019)
Participatory Development Planning in Banjarmasin (Case Study Correspondence between Banjarmasin Workplan with Results of Development Planning Consensus in 2016 at the Central Banjarmasin District. Government Work Plan (RKPD) is a document of the annual development planning designed to ensure relevance and consistency between planning, budgeting, implementation and monitoring as well as an integral part in the stage of preparation on Local Budget and Revenue Draft. This research aims to know how the follow-up on public participation in the form of the proposals in development planning consensus’ results document, causes of the discrepancy, as well as the government’s efforts for the creation of correspondence between Banjarmasin Workplan with Central Banjarmasin District’s development planning consensus result. This research use qualitative descriptive method, as well as techniques of data collection is done through documentation and structured interview that based on Theory of Public Participation according to Cohen and Uphoff in Siti Irene (2011: 61) through a discussion of the two sub concepts of community participation: involvement in planning and involvement in the implementation outlined by several indicators. Based on the research, the authors conclude that the follow-up of public participation in the form of proposals in the outcome development planning consensus result document between Central Banjarmasin District to Banjarmasin Workplan as much as 43,173%. Keywords: participatory development, government workplan.